Extra - Intestinal Gastrointestinal Stromal Tumor of Omentum - S Basnet; A Lakhey (Association of Clinical Pathologists of Nepal, 2014)
Gastrointestinal stromal tumors are rare tumors, constituting less than 3% of all gastrointestinal malignant neoplasms but are the most common mesenchymal tumors of the gastrointestinal tract. Approximately 10% of gastrointestinal stromal tumors are extraintestinal and mostly arise from the mesentery or omentum. Here we report a rare case of an extraintestinal gastrointestinal stromal tumor of mesentery. Morphological and immunohistochemical features led to a diagnosis of extra-gastrointestinal stromal tumor. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11610 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 682-684